[Goðafoss in North Iceland] - Streng, Evelyn Fiedler (1975)
Photograph of the Goðafoss Waterfall in North Iceland. The short waterfall is connected to a grey river cutting through the brown, rocky landscape. Brown hills cover the background, visible through the mist from the waterfall. Rocks peek through the water in the bottom right corner of the photograph.